Hyperglycemia and chorea. (29th May 2018) - Kashiura, Masahiro; Taira, Haruka; Amagasa, Shunsuke; Moriya, Takashi
Abstract : (A) Computed tomography of the brain showing no abnormal finding. (B) Magnetic resonance imaging of the brain showing a T1‐weighted area of hyperintensity in the left putamen, caudate nucleus, and globus pallidum with sparing of the internal capsule (arrow). (C) T2*‐weighted image showing hypointensity in the left putamen, caudate nucleus, and globus pallidum (arrowhead). (D) T2‐weighted image showing no abnormal finding.